A Study On Factors Affecting Labor Productivity Of Public Building Construction Project In Addis Ababa - Endeshaw Zeleke (My University, 2017)
Construction Industry Is A Major Player In Economy Of Any Countries By Generating Employment And Wealth To The Nations Through Its Forward And Backward Linkages With Other Sectors. However Many Projects In Developing Countries Experienced Extremely High Cost Overrun, Time Slippage And Low Quality. There Are So Many Different Factors That Result In Such A Problems In Building Construction Project But Productivity Is One Of The Most Important Factors Affecting The Overall Performance Of Any Construction Projects. Since Construction Productivity In Developing Country Like Ethiopia Is Highly Dependent On Labor Productivity The Objective Of This Study Is To Identify Factors Affecting Labor Productivity, Analyze And Rank These Factors Affecting Labor Productivity And Recommend Ways To Improve Labor Productivity Of Public Building Construction Project In Addis Ababa. To Achieve This Objectives Data Collection Was Carried Out Through The Review Of Literatures And Informal Discussion With Colleagues And Professionals In The Sector. Based On The Literature Review And Informal Discussion The Study Was Identified 52 Possible Factors Affecting Labor Productivity That Was Used For This Study. After Those Factors Was Identified A Questionnaire Was Designed By Categorizing Each Factors Under Eight Groups Namely 11Factors Under Management Related Factors,5 Under Tools And Equipment Related Factors,5Under Material Related Factors, 10 Under Manpower Related Factors, 7 Under Motivational Related Factors, 6 Under Technical Related Factors, 5 Under Subcontracting Related Factors And 3 Under External Factors. Then The Totals Of 50 Questionnaires Were Distributed To 30Public Building Construction Project Professionals In Addis Ababa. From A Total Of 50Questionnaires 44 Of Them Were Responded Correctly. Among 44 Respondents 29 Of Them Were From Contractor Side And 15 Of Them Were From Consultant Side.